2014
DOI: 10.3233/thc-140871
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood flow due to stented parent artery expansion in an intracranial aneurysm

Abstract: BACKGROUND: Stent placement is thought to obstruct the inflow of blood to an aneurysm. However, we introduced parent artery expansion and demonstrated that this may reduce the blood flow by the stent. In our previous study using idealized shapes, the results showed that flow reduction was greater than 22.2%, even if the expansion rate was only 6%. Furthermore, the parent artery expansion is predominantly caused by the effect of flow reduction as compared to that of flow reduction due to the obstruction of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In addition, many studies have found that changing the diameter [ 23 ], angle [ 24 , 25 ] and other geometric morphological characteristics of the parent artery can promote the healing of the aneurysm. Since the acquisition of geometric morphological parameters is simple, a more in-depth study of the geometric morphology of the parent artery is expected to guide clinicians in the process of treating cerebral aneurysms in real-time judgement of the rationality of the treatment strategy and the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have found that changing the diameter [ 23 ], angle [ 24 , 25 ] and other geometric morphological characteristics of the parent artery can promote the healing of the aneurysm. Since the acquisition of geometric morphological parameters is simple, a more in-depth study of the geometric morphology of the parent artery is expected to guide clinicians in the process of treating cerebral aneurysms in real-time judgement of the rationality of the treatment strategy and the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of stents is known to affect the blood vessel curvature. 27 Mori et al 28 29 demonstrated that expansion of the parent artery after stent implantation reduces flow. These changes in the parent artery depend on the mechanical properties of the stent; therefore, these mechanical properties should be considered as well as flow reduction effects during the design of an optimized stent.…”
Section: Discussionmentioning
confidence: 99%